Psychological conditions for improving the subjective quality of life in an extreme region - Kulik, Anastasiya Andreevna (2021)
The article presents summarized results of theoretical and empirical research on the problem of achieving and improving the subjective quality of life in an extreme region. One of the crucial factors influencing the assessments of the quality of life in various groups of respondents is found to be the principle of personal activity; the internal and external factors contributing to the “subject-environment” harmony are identified and a targeted model for achieving a high level of quality of life involving a combination of lifestyle parameters, personal resources, and external opportunities is proposed; the strategies of interaction within the “subject-environment” system in an extreme region at different levels of quality of life are described. The obtained results can give a start to new theoretical and empirical research on the specifics of the quality of life in different social groups and allow specifying the goals, objectives, directions, and the main ways of helping and assisting different segments of the population to ensure a high quality of life depending on both the nature of external influences and the subjective assessment of the environment.